Aflatoxin Decontamination in Maize Steep Liquor Obtained from Bioethanol Production Using Laccases from Species within the Basidiomycota Phylum - Marianela Bossa; María Silvina Alaniz-Zanon; Noelia Edith Monesterolo; María del Pilar Monge; Yamila Milagros Coria; Sofía Noemí Chulze; María Laura Chiotta (Toxins, 2024)
Maize (Zea mays L.) is an important crop in Argentina. Aspergillus section Flavi can infect this crop at the pre-harvest stage, and the harvested grains can be contaminated with aflatoxins (AFs). During the production of bioethanol from maize, AF levels can increase up to three times in the final co-products, known as, dry and wet distiller’s grain with solubles (DDGS and WDGS), intended for animal feed. Fungal enzymes like laccases can be a useful tool for reducing AF contamination in the co-products obtained from this process. The aim of the present study was to evaluate the ability of laccase enzymes included in enzymatic extracts (EE) produced by different species in the Basidiomycota phylum to reduce AF (AFB1 and AFB2) accumulation under the conditions of in vitro assays. Four laccase activities (5, 10, 15, and 20 U/mL) exerted by nine isolates were evaluated in the absence and presence of vanillic acid (VA), serving as a laccase redox mediator for the degradation of total AFs. The enzymatic stability in maize steep liquor (MSL) was confirmed after a 60 h incubation period. The most effective EE in terms of reducing AF content in the buffer was selected for an additional assay carried out under the same conditions using maize steep liquor obtained after the saccharification stage during the bioethanol production process. The highest degradation percentages were observed at 20 U/mL of laccase enzymatic activity and 1 mM of VA, corresponding to 26% for AFB1 and 26.6% for AFB2. The present study provides valuable data for the development of an efficient tool based on fungal laccases for preventing AF accumulation in the co-products of bioethanol produced from maize used for animal feed.